KONSEP PERSEKUTUAN UNIVERSAL DALAM UPACARA BARONG WAÉ ORANG MANGGARAI DITINJAU DARI PERSPEKTIF ENSIKLIK LAUDATO SI’ - Jean Loustar Jewadut; Alexander Jebadu; Ferdinandus Sebho (Bahasa Indonesia, 2026)
Environmental issues have become an important subject of studies among academics. One of the efforts taken to address these issues is to explore the richness of the indigenous cultures of traditional societies. This study aims to present the traditional wisdom of the Manggaraians in responding to environmental crises. The study presented in this article focuses itself on digging out the concept of universal communion in the ritual of Barong Waé of the Manggaraians in eastern Indonesia and gives a critical study on it in the perspective of universal communion of Laudato Si’ as one of official teachings of the Catholic Church on ecology. Data collected for this study are obtained by using in-depth interviews and studying available literatures. It was found that the concept of universal communion in Barong Waé Ritual of the Manggaraians is similar to the concept of ​​universal communion in the Encyclic of Laudato Si’. The richness of the concept of universal communion in the ritual of Barong Waé of the Manggaraians is juxtaposed with richness of the concept of universal communion in the Encyclic of Laudato Si and this juxtaposition can become a very valuable contribution to a pastoral ecology of the Catholic Church.